Experimental Study of Heat Transfer and Pressure Drop for H-type Finned Oval Tube with Longitudinal Vortex Generators and Dimples under Flue Gas. Issue 7 (9th May 2018) - Zhao, Xuebin; Tang, Guihua; Shi, Yuetao; Li, Yongkuan
ABSTRACT: To enhance heat transfer and reduce fouling of the finned-tube surface in economizers of coal-fired power plants, heat transfer and pressure drop characteristics for H-type finned oval tube with longitudinal vortex generators (LVG) and dimples, both in-line and staggered arrangements, are studied experimentally under flue dust condition. In addition, the ash samples and heat exchanger surfaces after the test are analyzed to help understanding the ash fouling and tube wear mechanisms. Compared to the original H-type finned oval tube, the Nusselt number of H-type finned oval tube bank with longitudinal vortex generators and dimples is improved by 34.5–41.7% (in-line arrangement) and 28.1–31.7% (staggered arrangement) within the studied Reynolds numbers, while the Euler number is increased by 21.9–28.3% (in-line arrangement) and 19% (staggered arrangement) in the clean finned-tube surface state. In the stable fouling state, the Nusselt number is improved by 37.7–42.3% (in-line arrangement) and 27.8–45.1% (staggered arrangement), while the Euler number is increased by 22.9–25.2% (in-line arrangement) and 33.3–42% (staggered arrangement). The results show that the novel fin structures can both inhibit fouling and enhance heat transfer effectively.